INTERNAL STAKEHOLDER VIEWS ON ISO 9001:2015 QUALITY MANAGEMENT SYSTEM: AN EXAMPLE OF HIGHER EDUCATION INSTITUTION - KANOĞLU, Mehmet Fatih (SSD Journal, 2021)
The quality management system is a management approach that aims to exceed the expectations of internal and external stakeholders, supports teamwork, and realizes the review and improvement of all units and activities. It is a system that aims to increase the quality and efficiency of the management as well as the products and services of the organization by giving priority to quality, according to the expectations of internal and external stakeholders. ISO 9001 standards; it emerged in the period when competitors increased and customer demands differed.Its purpose is to answer the question of how can I present the product to the customers with better quality than its competitors. It refers to the processes that cover the entire process of planning, implementing, controlling, taking action together with the status assessment of a product. Higher education institutions also apply ISO 9001:2015 Quality Management System in order to manage resources effectively and efficiently in accordance with stakeholder expectations in educationtraining, research-development, social contribution processes, and managerial and support processes. It tries to provide internal quality assurance with ISO standards. With this study, in which stakeholder expectations and opinions about the process are collected, it is aimed to determine the opinions of ISO 9001: 2015 QMS, which has been applied for one year in all academic and administrative units of a higher education institution, and to design preventive activities in accordance with stakeholder expectations. With the research, it is thought that the attitudes towards ISO are quite positive and that quality can be ensured with some additional measures and trainings.